DIGITAL TRANSFORMATION IN THE FMCG’S SALES AND DISTRIBUTION MANAGEMENT SYSTEM: ANALYSIS OF PERFORMANCE, ORGANIZATIONAL DYNAMICS, AND DIGITAL GOVERNANCE (A CASE STUDY OF JB DISTRIBUTOR IN WEST NUSA TENGGARA) - Bambang Triaji -; M. Adib Zata Ilmam; Natila Rizka Safitri (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
Digital transformation in distribution systems has become a strategic issue in the Fast Moving Consumer Goods (FMCG) industry, particularly in regions with limited infrastructure such as Nusa Tenggara Barat, Indonesia. This study aims to analyze the impact of Enterprise Resource Planning (ERP) and Sales Force Automation (SFA) implementation on distribution performance, as well as to examine the implications of digital governance in the context of regional distributors. A qualitative approach with an exploratory case study design was employed at CV. JB Distributor NTB. Data were collected through in-depth interviews with 12 informants, field observations, and document analysis, and analyzed using thematic analysis and before-after comparison. The findings indicate that digital transformation improves operational efficiency, data accuracy, and coordination across distribution functions. Data transparency enhances trust and reduces miscommunication among actors. However, latent conflict emerged during the early stages of implementation, particularly related to technological adaptation and changes in work practices. Digitalization also strengthens organizational control over sales personnel, increasing accountability while potentially generating tension in labor relations. The study highlights that the success of digital transformation depends on both internal and external factors, especially digital infrastructure and technological literacy. Adaptive digital governance is therefore required to ensure inclusive and sustainable transformation. This research provides a context-sensitive understanding of FMCG distribution digitalization at the regional level